Technology Integration in Pesantren Management in the Era of Society 5.0: Integrasi Teknologi Dalam Manajemen Pesantren di Era Society 5.0 - Ramadan, Wildan Rizki; Astutik, Anita Puji (Indonesian Journal of Innovation Studies, 2026)
General Background Islamic boarding schools (pesantren) play a strategic role in developing Islamic character and contributing to socio-economic development in Indonesia. Specific Background Modernization in Society 5.0 requires pesantren to adopt technology-based management to optimize administrative, educational, and financial operations. Knowledge Gap Research exploring the specific challenges and systemic potential of technology integration in pesantren management within Society 5.0 remains strictly limited. Aims This study investigates technology integration within pesantren management while evaluating associated challenges and opportunities. Results Utilizing a Systematic Literature Review (SLR) across multiple academic databases with PRISMA guidelines, findings reveal that technology improves administrative efficiency, financial transparency, and educational delivery, despite constraints like infrastructure limits, cultural resistance, and low digital literacy. Novelty This evidence-based synthesis provides a holistic framework linking traditional Islamic values with modern digital management systems. Implications Technology integration enables pesantren to remain adaptive, progressive, and globally competitive while preserving foundational traditional principles. Keywords : Pesantren Management, Technology Integration, Society 5.0, Information System, Educational Quality Key Findings Highlights Digital platforms like management information systems and financial software enhance administrative accuracy, transparency, and stakeholder trust in Islamic boarding schools. Structural barriers including restricted infrastructure, cultural reluctance, and digital skill deficits present key obstacles to seamless modern technology implementation. Strategic external collaboration, infrastructure upgrades, and targeted digital training allow traditional religious institutions to maintain core values while attaining global competitiveness.